The effect of cotrimoxazole on experimental Cryptosporidium parvum infection in kids - Koudela, B; Boková, A (Veterinary research, 1997)
The prophylactic and therapeutic effects of the folic acid inhibitor cotrimoxazole (trimethoprim in combination with sulfamethoxazole) was tested in goat kids experimentally infected with Cryptosporidium parvum oocysts. Of the twenty-four 6-day-old kids inoculated with 6 x 10(6) oocysts of C parvum, ten kids were administered cotrimoxazole prophylactically at a dose 20 mg/kg per day of trimethoprim/100 mg/kg per day of sulfamethoxazole for 14 consecutive days beginning 1 day before infection. Six kids were therapeutically treated at the same dose of cotrimoxazole for 9 consecutive days beginning 5 days post infection, and eight kids served as untreated controls. Experimental C parvum infection caused a severe clinical disease with profuse watery diarrhea, oocysts shedding and intestinal lesions in all groups of kids. Total days and severity of diarrhea were similar for all groups of kids. However, the mean duration of oocysts shedding, mean number of cryptosporidia per ileal villus, and distribution of cryptosporidia in the intestine were increased in both groups of cotrimoxazole-treated kids. These findings indicate that cotrimoxazole failed to control cryptosporidiosis.
Keywords: ileum; nemoci skotu; kombinace léků trimethoprim a sulfamethoxazol; feces; Cryptosporidiosis; kryptosporidióza; kozy; Trimethoprim, Sulfamethoxazole Drug Combination; střevní sliznice; novorozená zvířata; nemoci koz; Anti-Infective Agents; Goat Diseases; antiinfekční látky; zvířata; Feces; Animals, Newborn; Cryptosporidium parvum; Cattle; Cattle Diseases; Goats; skot; Animals; Ileum; Intestinal Mucosa